1996
DOI: 10.1016/s0735-1097(96)00279-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of heart rate variability during long-term follow-up in patients with mild to moderate heart failure

Abstract: Heart rate variability analysis, as assessed by Poincaré plots, has independent prognostic value in patients with mild to moderate chronic heart failure and identifies an increased risk for all-cause and sudden cardiac death in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
2
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(107 citation statements)
references
References 28 publications
(34 reference statements)
6
96
2
3
Order By: Relevance
“…Seven of nine patients in the "complex" group died suddenly within 6 months of the recording. Brouwer et al examined the association between Poincaré plot patterns and outcome in patients with mild to moderate heart failure (16). Abnormal 24-hour Poincaré plots were the only HRV index that identified an increased risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Seven of nine patients in the "complex" group died suddenly within 6 months of the recording. Brouwer et al examined the association between Poincaré plot patterns and outcome in patients with mild to moderate heart failure (16). Abnormal 24-hour Poincaré plots were the only HRV index that identified an increased risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that autonomic nervous system abnormalities are associated with the severity of chronic heart failure and with poor outcome. [3][4][5][6] Little is known regarding autonomic nervous system functionality and PAH.…”
mentioning
confidence: 99%
“…In children with congenital heart disease, HRV is reduced compared to normal controls and is predictive of sudden cardiac death (23,24). Following cardiac surgery for congenital heart disease, HRV is further reduced and may remain reduced years after operation (23,25,26).…”
Section: Resultsmentioning
confidence: 99%